Cover crops influence the physical hydric quality of a tropical sandy soil under no-tillage cotton cropping - Pedro Luan Ferreira da Silva; Cássio Antonio Tormena; Fábio Rafael Echer; Camila Pereira Cagna; Caroline Honorato Rocha; Renato Paiva de Lima (Revista Brasileira de Ciência do Solo)
ABSTRACT Reduced stability and structural resilience expose sandy soils to physical degradation under intensive production systems. This study aimed to evaluate the influence of different cover crops (CC) under no-tillage system (NTS) cotton cropping, grown either individually or in combination, on the soil physical quality (SPQ) of a sandy loam Oxisol (Latossolo) in southeastern Brazil. To quantify the effects of CC on soil physical quality indicators, an experiment in randomized blocks design was implemented with the treatments: CC1: single cultivation of Ruzi grass; CC2: Intercropping of Pearl Millet + Ruzigrass; CC3: Intercropping of Pearl Millet + Velvet bean; CCMixture: Intercropping of Ruzi grass, Pearl Millet and Velvet bean; and Control: maintenance of spontaneous plants. Undisturbed samples were taken from layers 0.00-0.10, 0.10-0.20, 0.20-0.40 and 0.40-0.60 m, in which were determined the soil bulk density (Bd), total porosity (TP), available water (AW), soil penetration resistance (PR) and the least limiting water range (LLWR). According to the multivariate analyses, the CC2 treatment resulted in better SPQ compared to the other treatments. The LLWR, air-filled porosity (θAFP), and AW were responsible for differentiating the CC2 treatment compared to the other treatments evaluated. Regardless of treatments, values of Bd> 1.75 Mg m-3 result in loss of SPQ due to the significant increase in PR and decreases in AW and LLWR. In the CC3 and Control, there was a physical impediment caused by the increase in Bd in the 0.10-0.20 m layer, which could result in the confinement of cotton roots to the surface, making them more susceptible to water stress. Soil PR reached values greater than 2.5 MPa for water contents lower than the θPWP in most treatments. In treatment CC3, for water contents equivalent to the θPWP, the PR did not exceed 6 MPa, while for the other treatments, the PR reached values greater than 10 MPa. Only the PR was influenced using CC. Soil moisture is considered crucial to maintain PR below impeding values, determining the control of the physical quality of this sandy soil.